TIL therapy broadens the tumor-reactive CD8+ T cell compartment in melanoma patients - Kvistborg, Pia; Shu, Chengyi Jenny; Heemskerk, Bianca; Fankhauser, Manuel; Thrue, Charlotte Albæk; Toebes, Mireille; van Rooij, Nienke; Linnemann, Carsten; van Buuren, Marit M.; Urbanus, Jos H.M.; Beltman, Joost B.; thor Straten, Per; et al. (Oncoimmunology, 2012)
There is strong evidence that both adoptive T cell transfer and T cell checkpoint blockade can lead to regression of human melanoma. However, little data are available on the effect of these cancer therapies on the tumor-reactive T cell compartment. To address this issue we have profiled therapy-induced T cell reactivity against a panel of 145 melanoma-associated CD8 + T cell epitopes. Using this approach, we demonstrate that individual tumor-infiltrating lymphocyte cell products from melanoma patients contain unique patterns of reactivity against shared melanoma-associated antigens, and that the combined magnitude of these responses is surprisingly low. Importantly, TIL therapy increases the breadth of the tumor-reactive T cell compartment in vivo, and T cell reactivity observed post-therapy can almost in full be explained by the reactivity observed within the matched cell product. These results establish the value of high-throughput monitoring for the analysis of immuno-active therapeutics and suggest that the clinical efficacy of TIL therapy can be enhanced by the preparation of more defined tumor-reactive T cell products.